Berberine Combined with Triple Therapy versus Triple Therapy for Helicobacter pylori Eradication: A Meta-Analysis of Randomized Controlled Trials. (4th October 2018) - Jiang, Xiaotao; Jiang, Chenguang; Huang, Cihui; Chen, Guoming; Jiang, Kailin; Huang, Baoyi; Liu, Fengbin
Abstract : Objective . To assess the effects and safety of berberine combined with triple therapy on Helicobacter pylori ( H. pylori ) eradication in adults. Methods . PubMed, MEDLINE, EMBASE, Cochrane Library, and Chinese databases including China National Knowledge Infrastructure (CNKI), Wanfang data, Chinese Technology Journal Full-text Database (VIP), and China biomedical literature database (CBM) were searched to obtain the eligible studies published up to October 10, 2017. The primary outcome was eradication rate of H. pylori . The secondary outcome was incidence of adverse effects. Data analysis was conducted by RevMan5.2 and Stata V.9.0 software. Trial sequential analysis (TSA) was performed to assess the risk of random error and the validity of conclusion with TSA program version 0.9 beta. Results . The meta-analysis results indicated berberine combined with triple therapy could improve the eradication rates of H. pylori (urea breath test subgroup: RR=1.18, 95%CI=(1.12, 1.24), P < 0.00001, biopsy subgroup: RR=1.23, 95%CI=(1.13, 1.34), P < 0.00001 ) and reduce the total occurrence of adverse effects (OR=0.59, 95%CI(0.46, 0.75), P < 0.0001 ) when compared with only using triple therapy. Besides, the incidence of nausea (OR=0.59, 95%CI(0.41, 0.86), P < 0.05 ) and diarrhea (OR=0.41, 95%CI(0.24, 0.71) was remarkably lower in experimental group while that of abdominal distention (OR=0.64, 95%CI(0.40, 1.04), P > 0.05 ) and vomiting (OR=0.65, 95%CI(0.37, 1.15), P > 0.05 ) had no significant change. TSA of H. pylori eradication rates and adverse effects incidence illustrated that the cumulative value of Z-curve went across the conventional boundary value, trial sequential monitoring boundary for benefit, and required information size, suggesting the results were stable. Conclusion . Evidence from meta-analysis suggested that berberine combined with triple therapy can be an option for increasing H. pylori eradication rates and reducing overall therapy-related adverse effects incidence, particularly nausea and diarrhea, whereas more randomized controlled trials designed according to CONSORT statement are demanded to support the efficacy in further studies.